Comparison Thermal Efficiency and Fuel Consumption of Electric Supercharger Variations For Otto Engine E70 - Endah Purwanti; Rosid Rosid; Sonny Faizal (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2018)
A Pressure Wave Supercharger (PWS) is a technical way to increase the incoming pressure on a diesel engine. PWS utilizes hot cylinder exhaust gas energy to build in air pressure such as conventional turbo filling. In normal combustion the air and fuel mixture will burn perfectly if a stoichiometric mixture, gasoline fuel can be said to be stoichiometric if to burn 1 kg of fuel requires 14.7 kg of air. While the engine rotation is high, it requires a lot of fuel while the intake air is limited in number. Based on this description, an examination of air intake into the intake manifold is required with an Electric Supercharger which functions as an air compressor. Using the Otto engine with modifications to the piston, compression ratio, ignition timing, injection duration and E70% bioethanol fuel. With the installation of these tools, can get the characteristics of combustion and improve the problems that occur associated with a rich mixture so that the engine performance becomes optimal and exhaust emissions become minimal. The result of variations in Electric Supercharger voltage at 6 volts, 8 volts and 10 volts can be seen that the best performance such as bmep, thermal efficiency has increased respectively by 14.73%, 22.87%, and sfc has decreased by 23, 84%.